2018
DOI: 10.1021/acs.energyfuels.8b01157
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effects of Montmorillonite on Coke Formation during Thermal Conversion of Heavy Oil

Abstract: In situ combustion is an enhanced method to recover heavy oil. The formation and oxidation of coke are crucial to promote the combustion front. Heavy oil from China and montmorillonite, a major type of clay, were used as samples in this study. The thermogravimetric analyzer (TGA) was applied to temperature-programmed oxidation/pyrolysis experiments to study the effect of montmorillonite on the thermal conversion characteristics of heavy oil. A fixed-bed reactor was then used to obtain coke and study the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…3 ISC is the oldest member of the ThEOR family, and its effectiveness for heavy oil recovery has been proved by many economically successful field applications since the 1920s. 4,5 It is basically an air injection process into reservoirs to in situ create a combustion front to push oil to move to producers through multiple displacement of steam drive, distillation, flue gas flood, hot and cold water drive, and so forth. 6−8 In comparison to other ThEOR processes, ISC has many unique assets including the following: high thermal efficiency because of the in situ generation of heat, the most readily available and low-cost injectant (air) regardless of the reservoir location, applicability for a variety of reservoir settings (light and heavy oils and shallow and deep reservoirs), high recovery efficiency benefiting from many combined displacement mechanisms, and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ISC is the oldest member of the ThEOR family, and its effectiveness for heavy oil recovery has been proved by many economically successful field applications since the 1920s. 4,5 It is basically an air injection process into reservoirs to in situ create a combustion front to push oil to move to producers through multiple displacement of steam drive, distillation, flue gas flood, hot and cold water drive, and so forth. 6−8 In comparison to other ThEOR processes, ISC has many unique assets including the following: high thermal efficiency because of the in situ generation of heat, the most readily available and low-cost injectant (air) regardless of the reservoir location, applicability for a variety of reservoir settings (light and heavy oils and shallow and deep reservoirs), high recovery efficiency benefiting from many combined displacement mechanisms, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The ISC technique has been given much attention recently for heavy oil recovery . ISC is the oldest member of the ThEOR family, and its effectiveness for heavy oil recovery has been proved by many economically successful field applications since the 1920s. , It is basically an air injection process into reservoirs to in situ create a combustion front to push oil to move to producers through multiple displacement of steam drive, distillation, flue gas flood, hot and cold water drive, and so forth. …”
Section: Introductionmentioning
confidence: 99%
“…It was found that the coke deposition in pores turned large pores into micropores which deteriorated permeability. A series of experiments were conducted to understand coke formation under different reaction conditions , and the presence of montmorillonites and nanoparticles . Yu et al in 2017 concluded that clay could accelerate reaction rates and improve an ignition process .…”
Section: Css Follow-up Processes and Simulationmentioning
confidence: 99%
“…Because the heavy oil coking process includes many serial and parallel reactions, the coking characteristics of heavy oil are complex. The coke yield from heavy oil is influenced by the coking temperature, oxygen concentration, heating rate, pressure, and so forth. ,, Meanwhile, the coke yield and reaction kinetics of coking reactions differ with different heavy oils. , Therefore, to systematically predict the influence of various conditions on heavy oil coking, it is necessary to establish an appropriate coke formation model.…”
Section: Introductionmentioning
confidence: 99%